Differential metabolic and coexpression networks of plant metabolism. (May 2015) - Omranian, Nooshin; Kleessen, Sabrina; Tohge, Takayuki; Klie, Sebastian; Basler, Georg; Mueller-Roeber, Bernd; Fernie, Alisdair R.; Nikoloski, Zoran
Highlights We examine the conclusions from different network-based analyses of plant metabolism. Specialized and nonspecialized plant metabolisms have different coexpression patterns.